Determination of Load for Quasi-static Calculations of Railway Track Stress-strain State - Kurhan, D. (Acta Technica Jaurinensis, 2016)
When calculating the railway track stress-strain state one usually assumes that total strains are brought immediately from applied load and the process dynamics is taken into account by the respective levels of design force. The dynamic component of the design force depends on various factors that are not always taken into account to the full. The analytical analysis of the calculation methods and the experiment testing data resulted in the following recommendations: for freight trains, especially in the conditions of soft rail support, it is advisable to take into account the effect of adjacent wheels; for modern passenger cars there is no significant load dependence on speed, and the main factor of dynamic component is the track fluctuations.